Myths and maths: Macroeconomic effects of fiscal adjustments in Hungary - Ágnes Horváth; Zoltán M. Jakab; Gábor P. Kiss; Balázs Párkányi (Magyar Nemzeti Bank, 2006)
In this paper we investigate the possible effects of fiscal tightening in Hungary from two perspectives. First, simulations in an estimated neo-Keynesian model are used to characterise the effects of different scenarios for fiscal consolidations. We show that the composition of fiscal shocks is important for both the economic outcome and monetary policy. These simulations suggest a modest output cost of fiscal consolidation. Then we take a closer look at the non-Keynesian effects and their relevance for Hungary in a qualitative way. In our review of non-Keynesian channels of fiscal adjustments we conclude that expansionary effects are likely to become evident only in the medium or long run, rather than immediately after measures are taken.
Keywords: E17; E52; E61; E62; E63; E65; H30; 330; Keynesian; non-Keynesian effects; expansionary fiscal adjustment; Monetary policy reactions; Model simulations; Haushaltskonsolidierung; Wirkungsanalyse; Schock; Geldpolitik; Keynesianismus; Ungarn